Peran Pemerintah Daerah dalam Penanggulangan Banjir di Kota Tanjungpinang - Esti Sulistiowati; Yudhanto Satyagraha Adiputra; Ardi Putra (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Implementing disaster management is a series of efforts that include establishing development policies that are at risk of disasters, disaster prevention activities, emergency response and rehabilitation. Currently several areas in Tanjungpinang City have the potential for flooding, only the Tanjungpinang City District and Bukit Cermin sub-district are free from flooding. According to him, there are many causes of waterlogging, such as inadequate drainage, rubbish blocking ditches, and housing that does not have drainage channels, the water drainage system needs to be repaired. The flow of water in the drainage must be clear so that it does not overflow onto the roads and into residential areas. The aim of the research is to determine the efforts made by the local government in dealing with floods in Tanjungpinang City. Then in this research the researcher refers to Ndraha (Labolo, 2010:36). The method in this research is that the author uses a qualitative descriptive research type using interview and observation data collection techniques. Based on the research, it can be concluded that the Regional Government in Flood Management in Tanjungpinang City has played a role. The following research results show that the government's role as a regulator is by making rules or regulations in disaster management, which are stated in the Tanjungpinang City Regional Regulation (PERDA) Number 03 2016 concerning the Implementation of Disaster Management. The role of the dynamist is to provide intensive and effective guidance and direction to agencies and communities related to disaster management. The government's role is as a facilitator by carrying out prevention efforts and providing facilities due to the impact of flooding.